The humiliation of sinners : public penance in thirteenth-century France - Mansfield, Mary C., 1960-1989 (Cornell University Press, 1995)
Annotation The Humiliation of Sinners is the work of a formidable scholar whose intensive research ... produced a bold reinterpretation of the history of medieval penance. - Catholic Historical Review "Mansfield's book challenges long-held assumptions about the disappearance of public penance after the Fourth Lateran Council in 1215. ... The Humiliation of Sinners shows that Mansfield was a young woman of extraordinary promise in the field of medieval studies."--Choice "Mansfield argues that public penance continued to flourish throughout the thirteenth century. ... She examines a rich variety of sources drawn primarily from northern France. The surviving narratives report a surprising number of cases of public penance involving notorious figures." - Law and History Review "This book is a major achievement. Its masterly synthesis is extensively documented, based on very close reading of a wide range of manuscript and printed material. Coherent in itself, it contains much of value beyond its own immediate concerns." - French History This compelling book, first published in 1995, changed historians' understanding of the history of public penance, a topic crucial to debates about the complex evolution of individualism in the West. Mary C. Mansfield demonstrates that various forms of public humiliation, imposed on nobles and peasants alike for shocking crimes as well as for minor brawls, survived into the thirteenth century and beyond